Collective Consciousness in Safeguarding Forestry in Richard Powers’ The Overstory (2018) - Annadhif Rafii Athallah; Hamzah Hamzah (English Language and Literature, 2020)
This thesis is an analysis of a novel written by Richard Powers entitled The Overstory (2018). It explores the issue of collective consciousness against the destruction of forest. The concept of eco-criticism by Thomas K. is applied to analyze this novel. This analysis focuses on how the concept of collective consciousness is used to prevent deforestation in several characters. This analysis also depends on the character to determine which chapter of the novel are used as the data. The result of the study shows that the characters employ several collective methods to fight against illegal logging in form of protest, petition, and, restoration of nature. In conclusion, collective consciousness can be also applied to prevent destruction of the forest